Almost settled : jewelling at the edges of place : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Fine Arts at Massey University, Te Whanganui-a-Tara, Aotearoa New Zealand - Wilce, Dawn (Massey University, 2026)
I’m from Wales but with few close relatives anchoring me to my homeland, I migrated to Aotearoa New Zealand in 2018. My Britishness offered me reassurance and familiarity, yet I also came to see how my heritage complicated the act of settling. After the occasional embarrassing cultural misstep, came humility and a desire to know more about this place I wanted to call home. This marked the beginning of a slow, reflective process to figure out how to operate in the context of a new place and what it means to belong. Several months after moving to the hilly northern suburbs of Wellington, I decided that my arthritic back felt strong enough to walk the 4.2km route to collect my youngest from school. From the footpath I noticed how the mailboxes on one street leaned at a curious angle into an absent wind. I found the little community book exchange built into the mossy bank near the dairy and wondered who else might enjoy the books I’d never got around to reading. My eyes scanned the silent windows of the old villas and squinted at the litter jewelling the edge of the park. I picked up a shard of a broken brake light, stopped and held it to the light, and saw the irony. I stepped only within the lines of the terracotta pavers and the bitumen seams of past repairs, and finally I thought about how Admiralty Street got its name. Abandoning my car that day allowed me to slow down and reorient myself with my locality. What had been a blur of nothingness as I raced towards the school bell became textured, dimensional, alive. I realised that it was the ordinary, nuanced characteristics that distinguished this place from the other places I had known. This experience forms the foundation of my art practice research, which is grounded in locality as a lived and situated experience. As the artist, my narrative is inevitably shaped by my own position and perspective of the place that I occupy. I am less interested in telling people what to see than in offering how to see for themselves: to notice what is often hidden in the everyday, to attend to what is taken for granted, to look more critically at our surroundings and ourselves. In doing so, perhaps this may provide an opportunity for others to explore assumptions about identity and place.
Figures are reproduced with permission.
Keywords: 360602 Fine arts